ACSF2-PGK1 interaction promotes ferroptosis in renal tubular epithelial cells of diabetic nephropathy by regulating Keap1/Nrf2 signaling - Xinran Liu; Chaoyi Chen; Sai Zhu; Xiaomei Luo; Li Gao; Ziyun Hu; Yu Ma; Ling Jiang; Yonggui Wu (Redox Report, 2025)
Objectives Recent studies have highlighted the strong association between kidney disease and ferroptosis. However, the role of ferroptosis in diabetic nephropathy (DN) remains unclear. This study aimed to determine the role of ACSF2 in renal tubule injury in DN and its underlying mechanisms.Methods We established diabetic kidney disease models both in vivo, using db/db mice, and in vitro, using high glucose induced HK-2 cells.Results A significant upregulation of ACSF2 was observed in the renal tubules of patients with DN and db/db mice. ACSF2 expression correlated with renal tubule injury and renal function, indicating its potential as an independent biomarker in patients with DN. Silencing ACSF2 alleviated high glucose-induced renal tubular epithelial cell injury by reducing oxidative stress-induced ferroptosis in vivo and in vitro. Mechanistically, liquid chromatography-tandem mass spectrometry and co-immunoprecipitation demonstrated that ACSF2 specifically binds to PGK1. ACSF2 affected Keap1 dimerization by regulating PGK1 phosphorylation at serine 203, which subsequently affects the levels of NRF2. Moreover, PGK1 stabilizes ACSF2 via deubiquitination, establishing a positive feedback loop. The results provide evidence that the interaction between ACSF2 and PGK1 promotes DN progression by regulating oxidative stress-induced ferroptosis.Discussion ACSF2 participates in crosstalk between oxidative stress and ferroptosis. This could be a potential therapeutic target for DN.